PERKEMBANGAN PERS MINAHASA PADA MASA KOLONIAL TAHUN 1869-1942 - Talumewo, Bodewyn Grey (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
This scientific paper contains about the development of the Minahasan press in the Netherlands’ colonial rule in the time of Dutch East Indies (of Indonesia). Explain about the origin of the press in Minahasa land when the newspaper of Tjahaja Sijang published since year 1869, about the development of the Minahasan press in Dutch East Indies, explain about develompment of the Minahasan press tandem with the national movement for freedom and for the independence of the Indonesia. Exposure of the pioneers and leaders of the Minahasan press in the colonial time. Keyword: press, colonial, Minahasa, North Sulawesi, kawanua, newspaper, journalism